2014
DOI: 10.1063/1.4866667
|View full text |Cite
|
Sign up to set email alerts
|

A well-structured metastable ceria surface

Abstract: Impact of near-surface native point defects, chemical reactions, and surface morphology on ZnO interfaces

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 34 publications
4
15
0
Order By: Relevance
“…The spot profile analysis for PDA temperatures up to 660 • C yields the same results within experimental error (independent of the annealing temperature). An average step height of d = (3.09 ± 0.05)Å close to the bulk value of CeO 2 (111) crystal plane spacing (c CeO 2 = 3.124Å) is determined in accordance with recent studies by non-contact atomic force microscopy 48 . Furthermore, the average terrace width ( Γ = (6.0 ± 0.5) nm) does not change significantly in this temperature region.…”
Section: Spa-leedsupporting
confidence: 85%
See 1 more Smart Citation
“…The spot profile analysis for PDA temperatures up to 660 • C yields the same results within experimental error (independent of the annealing temperature). An average step height of d = (3.09 ± 0.05)Å close to the bulk value of CeO 2 (111) crystal plane spacing (c CeO 2 = 3.124Å) is determined in accordance with recent studies by non-contact atomic force microscopy 48 . Furthermore, the average terrace width ( Γ = (6.0 ± 0.5) nm) does not change significantly in this temperature region.…”
Section: Spa-leedsupporting
confidence: 85%
“…For PDA temperatures above 660 • C, the oscillating part of the FWHM curves is strongly diminished indicating the formation of large terraces beyond the resolution of our instrument. The smoothening of the ceria film surface, however, has also been observed in a NC-AFM study on similar films 48 with an overall morphology closely resembling that of a (111)surface of bulk ceria. 9,49…”
Section: Spa-leedsupporting
confidence: 53%
“…In previous work, we found that annealing the ceria film in UHV at temperatures above 1050 K yields the high-temperature surface morphology characterized by large atomically rough terraces18 and a strong (near-)surface reduction17. Step-wise annealing the sample in air yields similar results as demonstrated by the series of AFM images shown in Fig.…”
Section: Resultssupporting
confidence: 69%
“…For the first two annealing steps performed at 1080 K (Fig. 1(a)), remainders of pyramids dominating the low-temperature surface morphology are found as for films annealed in UHV18. After the fourth and in particular the fifth annealing cycle where the temperature is increased to 1100 K to accelerate the surface transformation, the surface is considerably flattened exhibiting mainly layered islands, some of them approaching a hexagonal shape (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation